Effects of High-Intensity Interval Training (HIIT) on Metabolic Health among Individuals with Insulin Resistance - Kania-Bonicka, Zofia; Wojtach, Klaudia; Dziechciarz, Oriana; Kałwak, Oliwia; Głowacka, Barbara; Mruzek, Hanna (Quality in Sport, 2025)
Introduction Insulin resistance (IR) is a key mechanism underlying metabolic syndrome, type 2 diabetes, non-alcoholic fatty liver disease, and cardiovascular disease. Its prevalence is rising worldwide, including in Poland, with many cases undiagnosed. Lifestyle strategies, especially physical activity, are essential. High-Intensity Interval Training (HIIT) has recently drawn attention as a time-efficient method with strong potential to improve metabolic health. Aim This study aims to evaluate the effects of HIIT on metabolic health in individuals with insulin resistance. The focus is on insulin sensitivity, glycemic control, lipid profile, blood pressure, and hepatic function, and compares HIIT with moderate-intensity continuous training (MICT). State of Knowledge HIIT involves repeated bouts of vigorous activity with recovery periods, usually at 80–100% of maximal heart rate. Evidence shows that it enhances glucose uptake, reduces HOMA-IR, lowers HbA1c, and improves lipid balance by decreasing LDL and raising HDL cholesterol. HIIT also reduces systolic blood pressure and improves liver parameters in non-alcoholic fatty liver disease. Benefits are often greater than or comparable to MICT, despite shorter training duration. The strongest effects occur when combined with weight reduction and dietary changes. Summary (Conclusions) HIIT is an effective non-pharmacological strategy for managing insulin resistance and related disorders. It improves glycemic control, lipid and blood pressure regulation, and markedly enhances insulin sensitivity. Thanks to its time efficiency and ease of integration into daily life, HIIT is a valuable therapeutic option that may significantly support prevention and treatment of insulin resistance in both clinical